A Systematic Observation of Early Childhood Educators Accompanying Young Children’s Free Play at Emmi Pikler Nursery School: Instrumental Behaviors and Their Relational Value - Sagastui, Jone; Herrán, Elena; Anguera, M. Teresa (Frontiers in Psychology, 2020)
A significant number of literature documents young children’s innate interest in discovering their surroundings and gradually developing more complex activities and thoughts. It has been demonstrated that when environments support young children’s innate interest and progressive autonomy, they help children acquire a self-determined behavior. However, little is known about the application of this evidence in the daily practice of early childhood educational settings. This study examines Emmi Pikler Nursery School, a center that implements an autonomy-supportive educational approach. We conducted a systematic observation of two experienced Pikler educators while they accompanied young children’s free play. Our objective was to assess: if educators’ instrumental action follows a systematic behavioral sequence, if specific relational behaviors support each instrumental action, and if educators display differentiated intervention levels concerning children’s free play through the adaptation of the relational dimension. We conducted a lag sequential analysis to find behavioral patterns and concurrences between the observed behaviors. Our findings indicate that educators perform systematic action sequences and that each of the instrumental actions of those sequences has a specific relational value. We conclude that educators display three differentiated intervention levels depending on the child and the circumstances of the moment, providing appropriate autonomy support and reinforcing children’s self-determination.